EXPLORING THE POTENTIAL OF NANOTECHNOLOGY IN DRUG DELIVERY SYSTEMS - Nawar Dohair Al Joaid, Sultan Saadi Almutairi, Ayed Khaled Alashjaee, Bader Senhat Alotaibi, Bader Hamed Alharthi, Abdulmajeed Abdullah Alothman, Ahmed Ali Harshan, Mohammad Abdulrahman Alzaiber, Fahad Safar Alotaibi ,,; Abdulrahman Falah Mohmmed Alharbi, Bdulrahman Ibrahim Mohammed Alhaidari, Sarah Bhni Alhali, Zaid Obeed Mobark Aldawsari, Hazal Saud Kaud Alotaby, Talal Hamoud Abdullah Al-osaimi, (Chelonian Research Foundation, 2022)
Nanotechnology has emerged as a transformative force in healthcare, particularly in the realm of drug delivery systems. The ability to engineer nanoparticles with precise size, shape, and surface properties has revolutionized the administration of therapeutic agents. This advancement addresses longstanding challenges in conventional drug delivery, such as poor solubility, limited bioavailability, and off-target effects. By harnessing the unique properties of nanomaterials, researchers have developed novel strategies to enhance drug efficacy while minimizing toxicity. Size and shape considerations are paramount in nanotechnology-based drug delivery, influencing cellular uptake, biodistribution, and pharmacokinetics. Moreover, surface characteristics play a crucial role in modulating nanoparticle interactions with biological molecules and tissues. Through meticulous design and engineering, nanocarriers can be tailored to target specific tissues or cells, offering unprecedented precision in drug delivery. Despite its immense potential, nanotechnology also presents challenges, including concerns about toxicity and regulatory oversight. Addressing these issues requires comprehensive research in nanotoxicology and robust regulatory frameworks. However, the promise of nanotechnology in revolutionizing personalized medicine and improving patient outcomes is undeniable. With ongoing advancements in nanomaterial synthesis, formulation techniques, and targeted delivery strategies, the future of nanotechnology-based drug delivery systems holds immense promise for transforming healthcare.